A Genus - Degree formula for Fano variety of linear subspaces on complete intersections - Đặng, Tuấn Hiệp (Quy Nhon University, 2024)
The goal of this paper is to study the genus and degree of the Fano variety of linear subspaces on a complete intersection in a complex projective space. Suppose that the expected dimension of the Fano variety is one, we propose and prove a genus - degree formula.